RANCANG BANGUN SISTEM CRM (CUSTOMER RELATIONSHIP MANAGEMENT) BERBASIS WEB DENGAN POLA MVC - Rika Nugraha (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The reflexology business competition, especially in Pontianak City is increasing. Therefore, a new strategy is needed to assist companies within managing customer relationships, so that they can increase customer loyalty and retain existing customers. One of the business strategies that can help manage customer relationships is using CRM technology. CEO Reflexology is one of the MSMEs located in Pontianak City who will implement CRM technology. The purpose of this research is to built a web-based system using the MVC pattern by implementing CRM as a marketing tool. The CRM features that will be implemented are SMS Marketing as a marketing tool to promote and provide the latest information related to product using the SMS Gateway API and the customer segmentation to group customers using the K-Means Clustering method based on the customer's RFM model. The results of the CRM implementation in this research were customer segmentation by obtaining 3 customer groups based on the level of customer loyalty and the results of the SMS gateway API implementation on the SMS Marketing feature successfully sent to the recipient. The results of this research is a customer relationship management system that has been functionally tested and obtained results in accordance with the functional design of the system. Meanwhile, the interface testing for the general public received a very good predicate with a percentage of 87.37%.